Implementing Triage Standing Orders in the Emergency Department Leads to Reduced Physician-to-Disposition Times. (15th June 2016) - Hwang, Charles W.; Payton, Thomas; Weeks, Emily; Plourde, Michelle
Abstract : Emergency departments (EDs) throughout USA have improvised various processes to curb the "national epidemic" termed ED "crowding." Standing orders (SOs), one such process, are medical orders approved by the medical director and entered by nurses when patients cannot be seen expeditiously, expediting medical decision-making and decreasing length of stay (LOS) and time to disposition. This retrospective cohort study evaluates the impact of SOs on ED LOS and disposition time at a large university ED. Results indicate that SOs significantly improve ED throughput by reducing disposition time by up to 16.9% (p = 0.04 ), which is especially significant in busy ED settings. SOs by themselves are not sufficient for a complete diagnostic assessment. Strategies such as having a provider in the waiting area may help make key decisions earlier.